Caso de estudo de sistema de emulação em hardware para aplicação com controlador lógico programável - Santos, Vitor Alexandre (2016)
This work is a case study of an industrial plant emulator implemented in FPGA (Field Programmable Gate Array), to simulate systems together with a PLC (Programmable Logic Controller). Based in manufacturing industry, practical results of an industrial process prototype are confronted with the results of an applied model in FPGA. The objective is to assist in testing application validation levels in development, approximation of factory floor conditions, optimization of control process and training in industrial automation based on PLC. As a proposal for the models, the research use characteristics of a closed loop speed control system and from this, a discrete system process, which uses as a basis a manufacturing process. Initially the bibliographic review presents works around simulation of systems and emulators based on reconfigurable hardware. Also are reviewed topics related to the manufacturing industry with the application of PLC, beside the GRAFCET modeling technique. Next, questions will set out questions about reconfigurable logic around FPGA devices. Following the explanation of the theme, we describe the used prototypes and the developed models developed in FPGA for the emulator. Finally the obtained data are compared. With the presentation of the results is possible to verify the similarity between the two systems, physical and modeling in the FPGA. The small differences detected in the results obtained, in some points of the simulation, are discussed at the end of the work.